2019
DOI: 10.1093/cvr/cvz039
|View full text |Cite
|
Sign up to set email alerts
|

In vivo ratiometric optical mapping enables high-resolution cardiac electrophysiology in pig models

Abstract: Aims Cardiac optical mapping is the gold standard for measuring complex electrophysiology in ex vivo heart preparations. However, new methods for optical mapping in vivo have been elusive. We aimed at developing and validating an experimental method for performing in vivo cardiac optical mapping in pig models. Methods and results First, we characterized ex vivo the excitation-ratiometric properties during pacing and ventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 39 publications
4
58
1
Order By: Relevance
“…(N = 5) pig hearts ex vivo comparing hearts pre-and post-Blebbistatin (concentration unknown). The findings by Brack et al (2013) and Lee et al (2019) are in agreement with our study. Fedorov et al (2007) reported that Blebbistatin does not have any effect onto electrical activity.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…(N = 5) pig hearts ex vivo comparing hearts pre-and post-Blebbistatin (concentration unknown). The findings by Brack et al (2013) and Lee et al (2019) are in agreement with our study. Fedorov et al (2007) reported that Blebbistatin does not have any effect onto electrical activity.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we found that, in agreement with the shorter APD, VF dynamics are faster and more complex in contracting rabbit hearts. Our findings confirm previous findings by Brack et al (2013) and Lee et al (2019), who found that ventricular electrophysiology is significantly different in beating vs. contraction-inhibited isolated rabbit and pig hearts uncoupled with Blebbistatin, respectively. More specifically, Brack et al (2013) found that Blebbistatin substantially prolonges (∼ 17 − 25%) the ventricular action potential in isolated New Zealand White rabbit hearts (N = 39), and increases the ventricular fibrillation threshold, or reduces the likeliness of inducing VF, at a concentration of 5µM.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Here we show that AP duration and morphology are comparable in slices from transmural core biopsies and tissue blocks from the same pig ventricular regions. Median APD values (117 ms and 111 ms in the biopsy and block slices, respectively) are slightly lower than previously published values in experimental works on multicellular preparations [40][41][42][43][44] , which could be explained by the fact that our pig samples come from www.nature.com/scientificreports/ piglets and young pigs. Indeed, in our APD measures we could observe a trend to shorter APD in those from piglets as compared to those from adult pigs.…”
Section: Discussioncontrasting
confidence: 70%
“…Ratiometry of Cardiogreen optical signals is difficult to achieve as they contain fast and slow components and their characteristics depend on the excitation/emission wavelengths [16,17]. The use of an optical-fibre array (4 × 4) allows the electrical activity of the heart to be recorded in vivo under physiological blood circulation [3]. However, in large animals or humans, the main disadvantage of this method is the small mapping area, which does not permit high-spatial-resolution mapping.…”
Section: Motion Artefact Elimination In Om In Situmentioning
confidence: 99%